PERAN KOMPETENSI PEDAGODIK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMP N 14 MERANGIN - Susanti, Evi; Saragih, Hasmailena; Ningsih, Retno Wahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of teachers’ pedagogical competence in improving learning quality at SMP Negeri 14 Merangin. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews with teachers, the principal/vice principal for curriculum, and students, complemented by classroom observations and document analysis of instructional plans and assessment records. Data were analyzed interactively through data reduction, data display, and conclusion drawing. Trustworthiness was ensured through source and technique triangulation and member checking. The findings indicate that pedagogical competence contributes significantly to learning quality through: (1) understanding students’ characteristics to adjust learning strategies, (2) structured lesson planning that clarifies learning goals and classroom flow, (3) active and communicative teaching practices that increase student engagement, (4) the use of learning media and technology to support concept visualization, although not yet consistently implemented, (5) formative assessment and specific feedback that help students improve understanding more quickly, and (6) reflective practice and follow-up actions that promote continuous instructional improvement. The study also highlights the need to strengthen the consistent use of instructional media/ICT and systematic follow-up based on assessment results (remedial and enrichment) to ensure more equitable and sustained improvements in learning quality.